An analysis of the use of badges in the SAPO Campus platform: the perspective of communities’ administrators (Revista Lusófona de Educação, 2018)
SAPO Campus is a social media platform for educational contexts based on the basic principles of Web 2.0 and social networks. The platform has a badge feature that allows community members to engage in gamification dynamics by creating, supporting and assigning badges. An analysis of the platform interaction data shows that, despite some cases of success in the use of badges, the great majority of users never used this feature, especially teachers. In order to understand the reasons behind this lack of use, a questionnaire was administered to 61 administrators of communities in SAPO Campus. The overall results show us that this feature was not used because administrators thought it was hard to implement with their students, especially in what concerns its planning and use in an engaging way. In this article we analyze the general preferences indicated throughout the questionnaire regarding this functionality, in order to understand which changes should be implemented to improve its use.Keywords: badges; SAPO campus; gamification.